Mifepristone for Treatment of Metabolic Syndrome: Beyond Cushing’s Syndrome - Díaz-Castro, Francisco; Monsalves-Álvarez, Matías; Rojo, Leonel E.; del Campo, Andrea; Troncoso, Rodrigo (Frontiers in Pharmacology, 2020)
An emerging body of evidence indicates that cortisol, the glucocorticoid product of activation of hypothalamic-pituitary-adrenal axis, plays a role in the pathophysiology of metabolic syndrome. In this regard, chronic exposition to cortisol is associated with adverse effects such as hyperglycemia, weight gain, hypertension, type 2 diabetes, among others. Mifepristone is the only drug available with anti-glucocorticoid properties, which is FDA-approved for glycaemia control in patients with Cushing's syndrome and type 2 diabetes. Mifepristone also has beneficial effects in animal models of diabetes and patients with antipsychotic treatment-induced obesity. However, the underlying molecular mechanisms are not fully understood. In this perspective, we summarized the literature regarding the beneficial effects of mifepristone in metabolic syndrome from animal studies to clinical research. Also, we propose a mechanism of the beneficial effects in insulin sensitivity which involved the regulation of mitochondrial function in muscle cells.